Acute whole-body electromyostimulation associated with dynamic exercises did not alter cardiac autonomic modulation and oxygen uptake in obese and eutrophic men - Gabriela Cassemiliano; Paula Angélica Ricci; Soraia Pilon Jürgensen; Bianca Cristina Domingos; Audrey Borghi-Silva (Motriz: Revista de Educacao Fisica, 2021)
Abstract Aim: To contrast the acute effects of whole-body electromyostimulation (WB-EMS) with sham associated with dynamic exercises on cardiovascular, ventilatory, metabolic, and autonomic responses in men with obesity and controls. Methods: A randomized cross-over and double-blind trial with nine eutrophic (23.6 years; 23 ± 1.4 kg/m2) and ten men with obesity (26 ± 4 years; 38 ± 7 kg/m2), who were randomized to receive WB-EMS-Sham or Sham-WB-EMS with 30 min of rest between protocols. WB-EMS protocol (Miha Bodytec®) was applied at the motor level, frequency = 85 Hz, pulse duration = 350 μs, cycle on = 6′; cycle off = 4′. Sham group performed the same exercises with the electric current turned off. Throughout both protocols, subjects executed two dynamic exercises of 5 minutes each (step-up and step down associated with shoulder flexion, and lunge exercise associated with elbow flexion) in the same order. R-R intervals and breath-by-breath respiratory gases analysis were collected during the protocols. Heart rate variability (HRV) indexes were obtained using linear and nonlinear analysis. The level of statistical significance was set at p < 0.05. Results: Regarding both exercises, participants with obesity presented reduced oxygen uptake, higher ventilation, respiratory rate, blood pressure, and Borg scores (p < 0.05) when contrasted with controls, as expected. However, no significant differences were found for HRV indexes between groups (p > 0.05). In addition, WB-EMS did not increase oxygen uptake or altered autonomic modulation when contrasted with sham in both groups (p < 0.05). Conclusion: Obesity has a negative impact on symptoms and functional capacity. However, WB-EMS did not acutely enhance oxygen uptake or HRV during exercise in a population with obesity.